Tafsir Perilaku Etis menurut Pemahaman Akademisi Akuntansi dilihat dari Perbedaan Gender - Kusumaningrum, Nurcahyaning Dwi; Paramitha, Nurina Adi; Makmun, Sukron; Poerwanti, Sari Dewi (Indonesian Accounting Literacy Journal, 2025)
This study aims to find out how the interpretation of ethical behavior according to the understanding of accounting academics is seen from gender differences. This research is a mix methods research with qualitative methods with a hermeneutic approach and quantitative methods with regression. Data collection techniques are carried out with interviews, observations, and documentation. The results show that accounting academics have a similar interpretation of the concept of ethics. It was also found that women accounting academics have a different and better interpretation compared to male accounting academics on accounting professionalism. The results of this study can provide evidence that there are differences between male and female accounting academics regarding ethical behavior and gender.